O przyborach toaletowych w okresie rzymskim na Pomorzu Wschodnim - Nadolska-Horbacz, Krystyna (Acta Universitatis Lodziensis. Folia Archaeologica, 1983)
The paper concerns the territorial distribution, chronology and co-occurence of the toilot utensils and other elements of burial furniture. The source material collected in the article comprises combs, picettea, mirros and scissors. Distribution of the finds in question reveals at least two regions coextensive with the areas of intensive habitation. The first region is situated in the lower Vistula basin, and the second - on Rega and Parsęta rivers. The latter tends to remove south-westwards to the Pyrzyce land. A distinct border runs along Słupia river and watershed line between Gwda and Brda rivers. Distribution of the cultural elements in question is in some way determined by the state of the advances of archaeological investigations in Pomerania. It seems therefore that the papers of this sort should be supported by the stronger grounds which are to be proviťteoť with the broadly outlined excavations of cemeteries as well as settlements from the Roman period.